The Role of the School Principal’s Strategic Vision in Achieving Organizational Excellence: An Analytical Study of Secondary Schools - Alulaime, Sondos Naif Ezzdeen (Journal of Educational and Psychological Sciences, 2024)
This study aimed to investigate the role of strategic vision of school principals in achieving organizational excellence: an analytical study of secondary schools. The descriptive analytical method was used, and the study community included all principals of government and private secondary schools affiliated with the Directorate of Ain Al-Basha, totaling (37) principals according to the annual report issued by the Ministry of Education for the year (2023). The study tool was distributed to all members of the study community. The study results showed that the level of possession of secondary school principals in Ain Al-Basha for strategic vision was moderate, with "Improving the quality of education" dimension ranked first with a high level, followed by "Developing teachers and staff" dimension with a moderate level, and finally "Enhancing the school environment" dimension with a moderate level. The level of organizational excellence among secondary school principals in Ain Al-Basha was also moderate, with "Institutional reputation" dimension ranked first with a high level, followed by "Interaction with the community", and there were no statistically significant differences in respondents’ estimates regarding the strategic vision of secondary school principals attributed to gender and years of experience, as well as no statistically significant differences in respondents’ estimates regarding the level of organizational excellence of secondary school principals attributed to gender and years of experience. There was a positive correlation between the strategic vision of the school principal and achieving organizational excellence. The study concluded with a set of recommendations, including organizing various community events and activities, such as open days at the school, workshops for parents, and meetings for the local community, to encourage effective participation by community members in school affairs.